Bleaching of melanin in the epidermis of South American fur seal and its application on enzyme immunohistochemistry - Silva,A.P. (2011)
The South American fur seal (Arctocephalus australis) is an amphibious marine mammal distributed along the Atlantic and Pacific coasts of South America. The species is well adjusted to different habitats due to the morphology of its fin-like members and due to some adaptations in their integumentary system. Immunohistochemical studies are very important to evaluate the mechanisms of skin adaptation due the differential expression of the antigens present in the tissue depending of the region of the body surface. However, its strongly pigmented (melanin) epidermis prevents the visualization of the immuno-histochemical chromogens markers. In this study a melanin bleaching method was developed aimed to allow the visualization of the chromogens without interfering in the antigen-antibody affinity for immunohistochemistry. The analysis of PCNA (proliferating cell nuclear antigen) index in the epidermis of A. australis by immunohistochemistry with diaminobenzidine (DAB) as chromogen was used to test the method. The bleaching of the melanin allowed to obtain the cell proliferation index in epidermis and to avoid false positive results without affecting the immunohistochemical results.